Preparation method of hydrogen-nitrogen separation membrane material based on size screening and affinity recognition

CN122399585BActive Publication Date: 2026-10-20泉州职业技术大学
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610884318.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-20
Estimated Expiration
2046-06-18

AI Technical Summary

Technical Problem

[0003]当前,氢气氮气分离膜材料主要有聚合物膜、无机膜、混合基质膜及二维膜等类型,但各自存在明显的技术短板:聚合物膜(如聚酰亚胺、聚砜)依靠高分子链段无规堆叠形成的孔道进行单一尺寸筛分,难以突破渗透率-选择性的权衡效应,且热稳定性和化学稳定性不足,无法适应工业苛刻工况

Benefits of technology

1、分离性能卓越:通过尺寸筛分单元与亲和识别单元的协同,构建了物理筛分+化学识别双重机制,并结合KA沸石原位缺陷修复,使成品膜H2渗透率≥500×10-7mol/(Pa·m2·s),H2/N2选择性≥13,H2纯度达99.999%以上,大幅突破传统膜的渗透率-选择性权衡上限。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a preparation method of a hydrogen-nitrogen separation membrane material based on size screening and affinity recognition. The method comprises the following steps: a size screening unit, an affinity recognition unit and a polymer matrix are combined to form a casting solution, a film is formed on a porous support and is heat-crosslinked and solidified, and finally, a zeolite is grown in situ at a film defect to be blocked. The application adopts a dual separation method of physical size screening and chemical affinity recognition, and adopts an in-situ defect repairing technology, so that the hydrogen-nitrogen separation membrane material has the performance of precise screening and rapid transmission. The hydrogen permeation rate of the finished film is greater than or equal to 500*10 ‑7 mol / (Pa*m 2 *s), the H2 / N2 selectivity is greater than or equal to 13, the H2 purity after separation can be higher than 99.999%, and the finished film can be stably operated for a long time under harsh working conditions such as high temperature and high pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gas separation membrane material technology, specifically to a method for preparing hydrogen and nitrogen separation membrane materials based on size sieving and affinity recognition. Background Technology

[0002] Hydrogen, as a clean and efficient secondary energy source, requires large-scale production, purification, and storage for its industrial application to be truly effective. In typical industrial scenarios such as ammonia cracking for hydrogen production and syngas purification, hydrogen (H2) often coexists with gases like nitrogen (N2). However, the molecular dynamics diameters of hydrogen and nitrogen are very similar (H2 approximately 0.289 nm, N2 approximately 0.364 nm), and their adsorption and diffusion behaviors in most membrane materials are also similar, making their separation extremely difficult. Membrane separation technology, due to its advantages of low energy consumption, ease of operation, compact design, and environmental friendliness, has become the mainstream technology in this field. The core bottleneck in separation performance lies in the structural design and fabrication level of the membrane materials.

[0003] Currently, hydrogen and nitrogen separation membrane materials mainly include polymer membranes, inorganic membranes, mixed matrix membranes, and two-dimensional membranes, but each has obvious technical shortcomings: polymer membranes (such as polyimide and polysulfone) rely on the pores formed by the random stacking of polymer chain segments for single-size sieving, making it difficult to overcome the trade-off effect of permeability and selectivity, and their thermal and chemical stability is insufficient, making them unsuitable for harsh industrial conditions. Among inorganic membranes, zeolite membranes utilize regular pores for size sieving, but precise control of pore size is difficult, and pore blockage or size inhomogeneity easily occurs, resulting in insufficient separation accuracy. In addition, the material is brittle and the preparation process is complex. Palladium membranes rely on the special affinity of palladium for hydrogen to achieve high-selectivity separation through adsorption-desorption, but after ultrathinning, pinhole defects are easily generated, and palladium raw materials are expensive and susceptible to poisoning by impurity gases, limiting their large-scale application. Hybrid matrix membranes attempt to combine inorganic fillers with polymers to leverage the advantages of both. However, poor interfacial compatibility and pore matching between the inorganic fillers and the polymer matrix easily lead to non-selective short-circuit permeation, making it difficult to truly realize the synergistic effect of size sieving and affinity recognition. While novel two-dimensional membranes (such as MXene and PCN nanosheet membranes) exhibit excellent permeation performance, their preparation processes are complex, defects are difficult to control, and long-term operational stability is insufficient, leaving them far from industrial application.

[0004] In summary, existing hydrogen-nitrogen separation membranes generally suffer from a single separation mechanism (relying solely on size sieving or affinity recognition), low transport rates, and easily degraded affinity functions in complex environments. Furthermore, their fabrication processes are complex and costly, and they lack long-term stability under industrial conditions such as high temperature, high pressure, and impurities, severely restricting their industrial application. Summary of the Invention

[0005] To address the aforementioned shortcomings of existing hydrogen-nitrogen separation membranes, this invention provides a method for preparing hydrogen-nitrogen separation membrane materials based on size sieving and affinity recognition. This method constructs a dual separation mechanism through the synergistic cooperation of a size sieving unit and an affinity recognition unit, and through in-situ defect repair, the prepared separation membrane material exhibits excellent separation performance and high stability. Furthermore, the preparation process is environmentally friendly, and the metal components are recyclable.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing hydrogen-nitrogen separation membrane materials based on size sieving and affinity recognition, comprising the following steps: S1: A casting solution is formed by combining a size sieving unit, an affinity recognition unit, and a polymer matrix; the size sieving unit has a pore structure that matches the molecular size of hydrogen and nitrogen to achieve physical size sieving; the affinity recognition unit contains metal nanoparticles and their carriers that have a specific affinity for hydrogen, and the metal nanoparticles serve as selective affinity sites to enhance the solubility of hydrogen in the membrane and provide interfacial diffusion channels, thereby achieving selective and rapid transport of hydrogen; S2: The casting solution is formed on a porous support and then thermally crosslinked and cured to form an initial composite membrane; S3: Defect repair of the initial composite membrane is carried out by in-situ growth method. The initial composite membrane is placed in zeolite precursor solution, so that zeolite grows on the membrane surface and at the tiny defects inside, and is transformed into zeolite with a pore size of less than 0.30nm to block the defects. Finally, a hydrogen-nitrogen separation membrane material with dual functions of size sieving and affinity recognition is obtained.

[0007] Furthermore, S1 specifically includes: modifying the size sieving unit to enhance its compatibility with the polymer matrix, thereby obtaining a modified size sieving unit; dispersing the affinity recognition unit to obtain a stable affinity recognition unit dispersion; dissolving the polymer matrix and mixing it with the modified size sieving unit and the affinity recognition unit dispersion in a certain proportion, and adding an initiator and a crosslinking agent to obtain a casting solution.

[0008] Furthermore, the size sieving unit is a composite of hydrogen-bonded organic framework HOF-16 and ZIF-8 zeolite, with a mass ratio of (1-2):1; the pore size of the hydrogen-bonded organic framework HOF-16 is 0.35-0.38 nm, and the pore size of the ZIF-8 zeolite is 0.34 nm; the affinity recognition unit is a composite of palladium nanoparticles and amino-functionalized graphene, with a mass ratio of 1:(3-5); the polymer matrix is ​​polyimide; the modifier used in the modification treatment is γ-aminopropyltriethoxysilane; the initiator is azobisisobutyronitrile; the crosslinking agent is N,N'-methylenebisacrylamide; and the porous support is a porous α-Al2O3 support with a pore size of 0.1-0.2 μm and a porosity of 40%-60%.

[0009] Furthermore, the modification process of the size sieving unit is as follows: the dried size sieving unit is added to deionized water and ultrasonically dispersed to prepare a size sieving unit dispersion with a mass concentration of 10%-15%; a modifier is added, the amount of which is 3%-6% of the total mass of the size sieving unit; the pH value of the size sieving unit dispersion is adjusted to 6.0-7.0, and the mixture is stirred and reacted at 50-60℃ for 1-1.5 hours to obtain the modified size sieving unit dispersion.

[0010] Furthermore, the dispersion treatment step of the affinity recognition unit is as follows: the dried affinity recognition unit is added to deionized water, a dispersant is added, and ultrasonic dispersion is performed to prepare an affinity recognition unit dispersion with a mass concentration of 8%-12%; a protective agent is added, the amount of which is 0.5%-1.0% of the total mass of the affinity recognition unit, and after stirring evenly, it is kept at a constant temperature of 30-40℃ for 1-2 hours to obtain a stable affinity recognition unit dispersion.

[0011] Further, the preparation steps of the casting solution are as follows: the dried polymer matrix is ​​dissolved in DMF and stirred at 70-80℃ to prepare a polymer matrix solution with a mass concentration of 15%-25%; the temperature is lowered to 40-50℃, and the modified size sieve unit dispersion and affinity recognition unit dispersion are added and stirred to mix; then an initiator and a crosslinking agent are added, with the amount of initiator added being 0.8%-1.5% of the polymer matrix mass and the amount of crosslinking agent added being 0.3%-0.8% of the polymer matrix mass; after stirring, ultrasonic degassing is performed to obtain the casting solution; wherein, the ratio of the pure substance mass of the added modified size sieve unit to the pure substance mass of the polymer matrix is ​​controlled to be 1:(4-6), and the ratio of the pure substance mass of the added affinity recognition unit to the pure substance mass of the polymer matrix is ​​controlled to be 1:(5-8).

[0012] Furthermore, in S2, the casting liquid is uniformly coated onto the porous support using a casting method, with a coating thickness of 50-150 μm; the film formation conditions are: temperature 25-35℃, relative humidity 40%-60%, and standing for 12-24 hours; the thermal crosslinking reaction temperature is 150-180℃, and the temperature is maintained for 1-2 hours.

[0013] Furthermore, the specific steps for defect repair are as follows: the initial composite membrane is soaked in dilute hydrochloric acid with a mass concentration of 2%-5%, washed with water, dried, and then placed in a NaA zeolite precursor solution. It is reacted at 60-70℃ for 2-3 hours to allow nanoscale zeolite nuclei to grow in situ at the defect site, and then transformed into KA zeolite with a pore size of 0.30nm to seal the defect.

[0014] Furthermore, the effective pore size range of the hydrogen-nitrogen separation membrane material is 0.30-0.38 nm, and the membrane thickness is 80-120 μm.

[0015] This invention provides a method for preparing hydrogen-nitrogen separation membrane materials based on size sieving and affinity recognition. The prepared hydrogen-nitrogen separation membrane material has the following beneficial effects: 1. Superior Separation Performance: Through the synergy of the size sieving unit and the affinity recognition unit, a dual mechanism of physical sieving + chemical recognition is constructed. Combined with in-situ defect repair of KA zeolite, the H2 permeability of the finished membrane is ≥500×10⁻⁶. -7 mol / (Pa·m 2 •s), H2 / N2 selectivity ≥13, H2 purity reaches 99.999% or higher, significantly breaking through the upper limit of the permeability-selectivity trade-off of traditional membranes.

[0016] 2. Outstanding stability and durability: The KH-550 interface modification enhances the compatibility between the filler and the polyimide matrix. Combined with in-situ grown rigid zeolite patches, non-selective defects are precisely sealed, enabling the membrane to operate stably for over 5000 hours under harsh conditions of -20℃ to 200℃, 1-12MPa, and impurities such as CO / CO2. It can still maintain structural integrity under short-term high-temperature (300℃) conditions, and its resistance to thermal shock fatigue and poisoning is significantly better than existing products.

[0017] 3. Green, environmentally friendly and cost-controllable: By using amino-functionalized graphene as a carrier, the amount of palladium used is greatly reduced, and the preparation process has no wastewater, waste gas and waste residue emissions; the organic components in the membrane material can be partially degraded under specific conditions, and the metal components can be recycled to reduce environmental impact, which meets the development needs of the green hydrogen energy industry. Detailed Implementation

[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] This invention provides a method for preparing hydrogen-nitrogen separation membrane materials based on size sieving and affinity recognition, comprising the following steps: S1: A casting solution is formed by combining a size sieving unit, an affinity recognition unit, and a polymer matrix; the size sieving unit has a pore structure that matches the molecular size of hydrogen and nitrogen to achieve physical size sieving; the affinity recognition unit contains metal nanoparticles and their carriers that have a specific affinity for hydrogen, and the metal nanoparticles serve as selective affinity sites to enhance the solubility of hydrogen in the membrane and provide interfacial diffusion channels, thereby achieving selective and rapid transport of hydrogen; S2: The casting solution is formed on a porous support and then thermally crosslinked and cured to form an initial composite membrane; S3: Defect repair of the initial composite membrane is carried out by in-situ growth method. The initial composite membrane is placed in zeolite precursor solution, so that zeolite grows on the membrane surface and at the tiny defects inside, and is transformed into zeolite with a pore size of less than 0.30nm to block the defects. Finally, a hydrogen-nitrogen separation membrane material with dual functions of size sieving and affinity recognition is obtained.

[0020] In this invention, S1 specifically includes: modifying the size sieving unit to enhance its compatibility with the polymer matrix, obtaining a modified size sieving unit; dispersing the affinity recognition unit to obtain a stable affinity recognition unit dispersion; dissolving the polymer matrix and mixing it with the modified size sieving unit and the affinity recognition unit dispersion in a certain proportion, adding an initiator and a crosslinking agent to obtain a casting solution. Modifying the size sieving unit allows for the grafting of chemical groups that strongly interact with the polymer matrix onto its surface, significantly improving the interfacial bonding between the originally incompatible inorganic filler and the organic polymer, and avoiding gas short-circuiting caused by interfacial voids; pre-dispersing the affinity recognition unit effectively prevents the aggregation and deactivation of palladium nanoparticles, ensuring its highly active dispersion state. The optimization of both components before composite formation ensures the uniformity and stability of each functional component in the casting solution, which is a prerequisite for obtaining a defect-free, high-performance composite membrane.

[0021] In this invention, the size sieving unit is a composite of hydrogen-bonded organic framework HOF-16 and ZIF-8 zeolite, with a mass ratio of (1-2):1. The pore size of the hydrogen-bonded organic framework HOF-16 is 0.35-0.38 nm, and the pore size of ZIF-8 zeolite is 0.34 nm. Both have precise size sieving capabilities, enabling the physical sieving of H2 and N2. The hydrogen-bonded organic framework HOF-16 has a certain degree of dynamic flexibility in its pores, which is conducive to the rapid permeation of gases. ZIF-8 zeolite has more rigid and regular pores, ensuring stringent sieving precision. The synergy of the two enables high throughput without sacrificing the ability to retain nitrogen. Preferably, the mass ratio of hydrogen-bonded organic framework HOF-16 to ZIF-8 zeolite is 1.5:1. This ratio can achieve precise matching of pore size, which can improve gas permeability through the dynamic pore structure of HOF-16 and enhance the size sieving accuracy through the regular pores of ZIF-8 zeolite, thus synergistically achieving the physical sieving of H2 and N2.

[0022] In this invention, the affinity recognition unit is a composite of palladium nanoparticles (Pd nanoparticles) and amino-functionalized graphene (NH2-GO) in a mass ratio of 1:(3-5). The palladium nanoparticles have a particle size of 5-15 nm. Utilizing their special affinity for H2, they act as selective affinity sites, enhancing the local solubility of hydrogen within the membrane and providing interfacial diffusion channels, thus enabling rapid H2 transport. The amino-functionalized graphene enhances the dispersibility of the palladium nanoparticles. The two-dimensional sheet-like amino-functionalized graphene provides a large anchoring surface for the palladium nanoparticles, physically isolating them from interparticle contact and completely solving the problems of easy aggregation and deactivation. Highly efficient affinity transport can be achieved with a very small amount of palladium, reducing the cost by more than 40% compared to pure palladium membranes. Simultaneously, the amino functional groups on the surface of the amino-functionalized graphene can form strong bonds with the polymer matrix, creating a seamless connection from the palladium particles to the carrier and then to the polymer matrix. This significantly enhances the mechanical strength and structural stability of the membrane, eliminating interfacial separation. Preferably, the mass ratio of palladium nanoparticles to amino-functionalized graphene is 1:4, which can achieve uniform dispersion of palladium nanoparticles, give full play to their affinity recognition effect with H2, and at the same time utilize the two-dimensional structure of amino-functionalized graphene to improve the mechanical strength and gas transport rate of the membrane.

[0023] In this invention, the polymer matrix is ​​polyimide (PI); the selection of high-temperature resistant polyimide as the polymer matrix provides the membrane with basic thermal and chemical stability.

[0024] In this invention, the modifier used in the modification treatment is any one of γ-aminopropyltriethoxysilane (KH-550), amino-terminated polyimide oligomers, or isocyanate compounds; the initiator is azobisisobutyronitrile (AIBN); and the crosslinking agent is N,N'-methylenebisacrylamide (MBA). The combined use of KH-550 modifier, AIBN initiator, and MBA crosslinking agent further enhances the integrity of the membrane from the perspectives of interfacial chemistry and network structure.

[0025] In this invention, the porous support is a porous α-Al₂O₃ support with a pore size of 0.1-0.2 μm and a porosity of 40%-60%; all raw materials have a purity of ≥98%. The selection of the porous α-Al₂O₃ support balances the requirements of mechanical support and gas transport. Its 0.1-0.2 μm pore size and 40%-60% porosity can effectively support the dense separation layer without becoming an additional obstacle to gas transport.

[0026] In this invention, the modification process of the size sieving unit is as follows: The dried size sieving unit is added to deionized water and ultrasonically dispersed (300-500W, 30-60 minutes) to prepare a size sieving unit dispersion with a mass concentration of 10%-15%; a modifier is added, with the amount added being 3%-6% of the total mass of the size sieving unit; the pH of the size sieving unit dispersion is adjusted to 6.0-7.0 using dilute hydrochloric acid or dilute sodium hydroxide solution, and the mixture is stirred and reacted at 50-60℃ for 1-1.5 hours to obtain the modified size sieving unit dispersion. Maintaining the dispersion mass concentration at 10%-15% and using high-power ultrasound ensures the complete dissociation and uniform dispersion of the size sieving unit particles. Most importantly, precisely setting the dosage of KH-550 modifier to 3%-6% of the total mass of the sieving unit, and maintaining a pH of 6.0-7.0, maximizes the hydrolysis and condensation efficiency of KH-550 modifier, allowing it to form a uniform and complete amino functional group coating layer on the surface of the sieving unit without damaging the pore structure of the sieving material itself due to excessively high or low pH. Reacting at 50-60℃ ensures the modification reaction proceeds at an appropriate rate, avoiding uneven coating caused by being too fast or too slow. The resulting modified sieving unit exhibits optimal dispersibility, affinity with the polymer matrix, and pore integrity.

[0027] In this invention, the dispersion process of the affinity recognition unit is as follows: The dried affinity recognition unit is added to deionized water, a dispersant (sodium dodecylbenzenesulfonate) is added, and ultrasonic dispersion is performed (300-500W power, 40-80 minutes) to prepare an affinity recognition unit dispersion with a mass concentration of 8%-12%. A protective agent (polyvinylpyrrolidone, PVP) is added at a concentration of 0.5%-1.0% of the total mass of the affinity recognition unit. After stirring evenly, the dispersion is kept at 30-40°C for 1-2 hours to obtain a stable affinity recognition unit dispersion. Preparing an 8%-12% concentration affinity recognition unit dispersion and using high-power, long-duration ultrasonication generates strong shear force, overcoming the van der Waals forces between palladium nanoparticles, efficiently dispersing and anchoring them onto the amino-functionalized graphene sheets. Adding 0.5%-1.0% of the total mass of the affinity recognition unit protective agent forms a steric hindrance layer on the surface of the dispersed palladium particles, preventing them from re-aggregating during subsequent stirring and storage. This series of operations ensures that the palladium nanoparticles retain their nano-activity and affinity for hydrogen to the maximum extent in the final membrane material.

[0028] In this invention, the preparation steps of the casting solution are as follows: the dried polymer matrix is ​​dissolved in DMF and stirred at 70-80℃ to prepare a polymer matrix solution with a mass concentration of 15%-25%; the temperature is lowered to 40-50℃, and the modified size sieving unit dispersion and affinity recognition unit dispersion are added and stirred; then the initiator and crosslinking agent are added, and after stirring, ultrasonic degassing is performed to obtain the casting solution. The ratio of the pure mass of the added modified size sieving unit to the pure mass of the polymer matrix is ​​controlled to be 1:(4-6), and the ratio of the pure mass of the added affinity recognition unit to the pure mass of the polymer matrix is ​​controlled to be 1:(5-8). This ratio is crucial for balancing membrane separation performance and mechanical integrity. If there is too much functional filler, the membrane material will become brittle and crack due to excessive internal stress; if there is too little, the separation function will be insufficient. This ratio range ensures that the two functional units are highly dispersed and optimally loaded in the continuous polymer phase, fully leveraging the dual synergistic separation effect while ensuring the membrane layer is flexible and dense. In addition, the amount of initiator added is 0.8%-1.5% of the polymer matrix mass, and the amount of crosslinking agent added is 0.3%-0.8% of the polymer matrix mass. The amount of initiator and crosslinking agent directly determines the density of the crosslinking network of the polymer matrix. The amounts of 0.8%-1.5% and 0.3%-0.8% can form a moderately crosslinked structure, which can fix the functional filler, enhance the anti-swelling and anti-plasticization ability, and avoid the membrane becoming too rigid and the flux decreasing due to excessive crosslinking.

[0029] In this invention, in step S2, a casting solution is uniformly coated onto a porous support using a casting method at a rate of 5-10 cm / min, resulting in a coating thickness of 50-150 μm. The film-forming conditions are: a temperature of 25-35°C and a relative humidity of 40%-60%, followed by standing for 12-24 hours to allow solvent evaporation and film formation. The temperature is then raised to 80-100°C and dried for 2-3 hours to remove residual solvent. The thermal crosslinking reaction temperature is 150-180°C, and the temperature is maintained for 1-2 hours. Using a casting method at a rate of 5-10 cm / min, a uniform liquid film with a thickness deviation within ±5 μm can be obtained. Standing for 12-24 hours in a mild and controllable environment of 25-35°C and 40%-60% allows for slow and uniform solvent evaporation, effectively avoiding defects such as pinholes and bubbles caused by rapid surface skinning or internal boiling. The membrane is then heated to 80-100℃ to dry, removing residual solvent, and then thermally crosslinked at 150-180℃ to allow the polymer segments to fully react with the crosslinking agent, thus completely solidifying and shaping the previously constructed bifunctional network and giving the membrane final mechanical strength and structural stability.

[0030] In this invention, the specific steps for defect repair are as follows: the initial composite membrane is soaked in a 2%-5% (w / w) dilute hydrochloric acid solution, washed with water, and dried. Then, it is placed in a NaA zeolite precursor solution and reacted at 60-70°C for 2-3 hours, allowing nanoscale zeolite nuclei to grow NaA zeolite in situ at the defect site. Subsequently, the membrane material is placed in a 1 mol / L KCl solution and soaked at 60°C for 4 hours to perform potassium ion exchange, converting the NaA zeolite into KA zeolite (effective pore size of 0.30 nm), thus sealing the defect. Soaking the initial composite membrane in dilute hydrochloric acid removes residual unreacted substances and impurities from the surface, providing a clean substrate for subsequent crystal growth. Placing it in a NaA zeolite precursor solution and reacting at 60-70℃ drives the preferential nucleation and growth of nanoscale zeolite nuclei at high-energy defect sites (such as pinholes and microcracks). Ultimately, these zeolite nuclei transform into KA zeolite with a pore size of only 0.30 nm, smaller than most permeate gas molecules, forming perfect molecular patches that precisely plug non-selective leaks while having relatively little impact on the pores of the membrane's main separation layer. This regionalized remediation technology significantly improves hydrogen / nitrogen selectivity without sacrificing hydrogen permeability and eliminates the risk of membrane failure caused by the expansion of tiny defects during pressure fluctuations or long-term operation, making it crucial for achieving a long membrane lifespan (≥5000 hours).

[0031] In this invention, the effective pore size range of the hydrogen-nitrogen separation membrane material is 0.30-0.38 nm, and the membrane thickness is 80-120 μm. The final effective pore size range of the membrane is 0.30-0.38 nm, which falls precisely between the molecular diameters of hydrogen (0.289 nm) and nitrogen (0.364 nm). The membrane thickness of 80-120 μm is an optimized result that minimizes the gas transport path and maximizes the flux while ensuring the membrane's mechanical strength. This dense separation layer of this thickness directly results in a hydrogen permeability ≥500 × 10⁻⁶. -7 mol / (Pa·m 2 With its excellent comprehensive performance of ·s) and hydrogen / nitrogen selectivity ≥13, it is fully qualified for application in actual industrial conditions such as ammonia cracking for hydrogen production and syngas purification.

[0032] The present invention provides a method for preparing hydrogen-nitrogen separation membrane materials. This method combines a precisely sized sieving unit with precise pore size and an affinity recognition unit capable of specifically adsorbing and rapidly transporting hydrogen with a polymer matrix. After membrane formation, defects are repaired by in-situ growth of ultra-small pore zeolite. This overall concept constructs a dual separation mechanism of physical sieving and chemical affinity recognition, and solves the problem of defect control in separation membranes, resulting in the following significant advantages: Firstly, regarding the formation of the pore structure, this invention does not rely on a single, difficult-to-control pore-forming process, but rather employs a dual synergistic strategy of intrinsic material pores and precise defect sealing: the size sieving unit is composed of a hydrogen-bonded organic framework (HOF-16) and ZIF-8 zeolite. HOF-16 is a porous crystalline material formed by hydrogen bonds, possessing an intrinsic pore size of 0.35-0.38 nm and an ordered pore structure. ZIF-8 zeolite is a zeolite-like metal-organic framework material with an intrinsic pore size window of approximately 0.34 nm. Therefore, the main pore sizes of the size sieving unit are concentrated between 0.34-0.38 nm, forming the main channels for gas transport within the membrane. However, during the membrane fabrication process, tiny non-selective pinholes or cracks inevitably occur between different components. The in-situ growth defect repair step of this invention grows KA zeolite with a pore size of only 0.30 nm at these defects (the pores of KA zeolite are smaller than most of the main pores, like a precise patch, only blocking defects larger than 0.38 nm), allowing hydrogen gas (0.289 nm) to pass through without blocking the original main screening channels; the final membrane has an effective pore size precisely controlled within an extremely narrow range of 0.30-0.38 nm, laying a solid structural foundation for efficient screening.

[0033] Secondly, this pore structure design allows hydrogen gas with a molecular diameter of 0.289 nm to pass through smoothly, while nitrogen gas with a diameter of 0.364 nm is trapped. The effective pore size of the separation membrane has a lower limit of 0.30 nm and an upper limit of 0.38 nm. The kinetic diameter of hydrogen gas, 0.289 nm, falls within the passable range of most pores, resulting in low transport resistance. Nitrogen gas, with a diameter of 0.364 nm, is close to or even exceeds the size of many pores. In particular, the inherent pore size window of ZIF-8 zeolite is approximately 0.34 nm, which can significantly hinder the mass transfer of nitrogen molecules. Combined with the regular pores of HOF-16 and the approximately 0.3 nm precise sieve layer formed by defect repair in KA zeolite, these three elements work together to form an effective barrier against nitrogen. Furthermore, the pore size of the defect-repaired KA zeolite is only 0.30 nm, which is completely insurmountable for nitrogen. Even with a small number of HOF-16 channels with pore sizes close to 0.38 nm within the membrane, nitrogen molecules experience severe confined diffusion resistance, resulting in extremely low permeation rates. Therefore, the separation membrane pore system of this invention synergistically constitutes a highly efficient selective channel for hydrogen and an effective barrier against nitrogen, which is the fundamental source of size sieving selectivity.

[0034] Finally, this invention utilizes the selective affinity enhancement transport mechanism of palladium nanoparticles. The promoting effect of palladium nanoparticles on hydrogen permeation is not a loss, but rather a significant increase in permeability through the following mechanisms: First, as selective hydrogen affinity sites, palladium nanoparticles preferentially adsorb and dissociate hydrogen molecules on the upstream surface of the membrane, forming a locally high-concentration enrichment region, increasing the effective concentration gradient across the membrane, and providing a stronger driving force for permeation. Second, the nano-interfacial region between the palladium nanoparticles and the polymer matrix, as well as the surface of the amino-functionalized graphene support, provides low-resistance hydrogen diffusion shortcuts; dissociated hydrogen atoms can be rapidly transported along these channels through surface diffusion and interfacial diffusion. The hydrogen transport rate in these interfacial channels is much higher than that in the polymer bulk. Compared to a single sieve membrane that relies solely on pressure difference to pass through the pores, palladium nanoparticles significantly increase the hydrogen permeation flux through the dual effects of enhanced solubility and providing a rapid interfacial diffusion path, without affecting the retention effect on non-affinity gases such as nitrogen. Therefore, it not only does not cause loss, but also significantly increases the hydrogen permeability.

[0035] The hydrogen-nitrogen separation membrane material prepared by the above method has applications including, but not limited to, ammonia cracking for hydrogen production, syngas purification, natural gas reforming for hydrogen production, CO2 sequestration associated gas separation, and shale gas extraction associated gas separation. Specific application methods are as follows: (1) Application in ammonia cracking for hydrogen production: Hydrogen and nitrogen separation membrane materials are assembled into membrane separation modules and placed in the separation unit of the ammonia cracking hydrogen production system. The separation temperature is controlled at 100-300℃ and the separation pressure is 1-10MPa. The feed gas (ammonia cracking gas, mainly composed of H2 and N2, containing a small amount of NH3) is fed at a rate of 1-5m 3 A flow rate of / h passes through the membrane module; the membrane material, through size sieving, prevents N2 (molecular diameter 0.364nm) permeation while allowing H2 (molecular diameter 0.289nm) to pass through. Simultaneously, relying on the affinity recognition of palladium nanoparticles, it specifically adsorbs H2 and accelerates its transport, achieving highly efficient separation of H2 and N2; after separation, the H2 purity is ≥99.999%, and the H2 permeability is ≥500×10⁻⁶. -7 mol / (pa m 2 s), H2 / N2 selectivity ≥13, can be directly used in fuel cells, semiconductors and other fields.

[0036] (2) Application in syngas purification: Membrane materials are assembled into membrane separators for the purification and separation of syngas (mainly composed of H2, CO, N2, and CO2). The separation temperature is controlled at 80-200℃, the separation pressure at 2-8MPa, and the syngas flow rate at 2-6m. 3 / h; The membrane material accurately distinguishes impurity gases such as H2, CO, and N2 through size sieving. At the same time, relying on the specific function of the affinity recognition unit, it improves the H2 transport rate and inhibits the permeation of impurity gases. After separation, the H2 purity is ≥99.99% and the H2 recovery rate is ≥98%, which can effectively reduce the energy consumption of subsequent purification processes and is suitable for the industrial needs of hydrogen production from syngas.

[0037] (3) Nitrogen separation during hydrogen pipeline scavenging: Membrane materials are applied to the separation of mixed gases (mainly H2 and N2) during scavenging in hydrogen pipelines and storage tanks. The separation temperature is controlled at 10-50℃, the separation pressure at 0.5-2MPa, and the mixed gas flow rate at 1.5-4m. 3 / h; The membrane material achieves efficient separation of H2 and N2 through the dual functions of size sieving and affinity recognition; H2 and N2 can be recycled after separation.

[0038] The following examples and comparative examples illustrate the beneficial technical effects of the hydrogen-nitrogen separation membrane material preparation method based on size sieving and affinity recognition of the present invention. In the following examples, the purity of the raw materials used was ≥98%; the porous α-Al₂O₃ support had a pore size of 0.15 μm and a porosity of 50%, and was rinsed with deionized water and ethanol and dried at 120°C for 3 hours before use; the palladium nanoparticles were pretreated by reduction to remove the surface oxide layer before use; all drying steps were carried out in a vacuum drying oven.

[0039] Example 1 This example provides a method for preparing hydrogen-nitrogen separation membrane materials based on size sieving and affinity recognition, including the following steps: S1: Raw material preparation. Size sieving unit: HOF-16 hydrogen-bonded organic framework (pore size 0.36nm) 90g, ZIF-8 zeolite (pore size 0.34nm) 60g, total 150g (mass ratio 1.5:1); Affinity recognition unit: palladium nanoparticles (particle size 10nm) 25g, amino-functionalized graphene 100g, total 125g (mass ratio 1:4); Polymer matrix (PI): polyimide 750g.

[0040] Modification of size sieve unit: 150g of size sieve unit was added to 850mL of deionized water and ultrasonically dispersed for 45min (power 400W) to prepare a dispersion with a mass concentration of 15%; 6.75g of KH-550 (accounting for 4.5% of the total mass of size sieve unit) was added, and the pH was adjusted to 6.5 with dilute hydrochloric acid. The mixture was stirred at 55℃ and 250r / min for 1.2h; the resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 150g of powdered modified size sieve unit.

[0041] Affinity recognition unit dispersion: 125g of affinity recognition unit was added to approximately 1450mL of deionized water, and 1.88g of sodium dodecylbenzenesulfonate (1.5% of the total mass of affinity recognition unit) was added. The mixture was ultrasonically dispersed for 60min (400W) to prepare a dispersion with a mass concentration of approximately 8%. 0.75g of PVP (0.6% of the total mass of affinity recognition unit) was added, stirred to dissolve, and allowed to stand at 35℃ for 1.5h. The resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 125g of powdered affinity recognition unit.

[0042] S2: Preparation of casting solution and film forming. 750g of PI was dissolved in 2250mL of DMF and stirred at 75℃ and 200r / min to prepare a PI solution with a mass concentration of 25%. The solution was cooled to 45℃, and 150g of the above-mentioned powdered modified size sieve unit and 125g of powdered affinity recognition unit were added. The mixture was stirred and mixed for 3.5h. 9g of AIBN (1.2% of the PI mass) and 3.75g of MBA (0.5% of the PI mass) were added, and stirring was continued for 1.5h. The mixture was then ultrasonically degassed for 25min (350W) to obtain the casting solution. The casting solution was cast onto a pretreated support at a rate of 7.5cm / min, controlling the wet film thickness to 100μm. The film was allowed to stand at 30℃ and 50% relative humidity for 18 hours to evaporate and form a film; then dried at 90℃ for 2.5 hours; and then thermally crosslinked by heating to 165℃ at 7.5℃ / min and holding for 1.5 hours to obtain the initial composite film.

[0043] S3: Defect Repair. After the initial composite membrane cooled to room temperature, it was soaked in 3.5% dilute hydrochloric acid at 27°C for 1.5 hours, washed with deionized water until neutral, and vacuum dried at 75°C for 2.5 hours. Then, it was placed in a NaA zeolite precursor solution and reacted at 65°C for 2.5 hours to allow the zeolite nuclei to grow in situ and form NaA zeolite. Subsequently, the membrane material was placed in a 1 mol / L KCl solution and soaked at 60°C for 4 hours to perform potassium ion exchange, converting NaA zeolite into KA zeolite (effective pore size approximately 0.3 nm), resulting in the finished membrane with a thickness of 100 μm and an effective pore size range of 0.30-0.36 nm.

[0044] Example 2 This example provides a method for preparing hydrogen-nitrogen separation membrane materials based on size sieving and affinity recognition, including the following steps: S1: Raw material preparation. Size sieving unit: HOF-16 hydrogen-bonded organic framework (0.36nm) 60g, ZIF-8 zeolite (0.34nm) 60g, total 120g (mass ratio 1:1); Affinity recognition unit: palladium nanoparticles (5nm) 20g, amino-functionalized graphene 60g, total 80g (mass ratio 1:3); Polymer matrix (PI): polyimide 600g.

[0045] Modification of size sieve unit: 120g of size sieve unit was added to 800mL of deionized water and ultrasonically dispersed for 30min (power 300W) to prepare a dispersion with a mass concentration of 13%; 3.6g of KH-550 (accounting for 3% of the total mass of size sieve unit) was added, and the pH was adjusted to 6.0 with dilute hydrochloric acid. The mixture was stirred at 50℃ and 200r / min for 1.5h; it was then vacuum dried at 60℃ to constant weight to obtain 120g of powdered modified size sieve unit.

[0046] Affinity recognition unit dispersion: 80g of affinity recognition unit was added to 920mL of deionized water, and 1.2g of sodium dodecylbenzenesulfonate (accounting for 1.5% of the total mass of affinity recognition unit) was added. The mixture was ultrasonically dispersed for 40min (power 300W) to prepare a dispersion with a mass concentration of about 8%. 0.4g of PVP (accounting for 0.5% of the total mass of affinity recognition unit) was added, stirred to dissolve, and allowed to stand at 30℃ for 2h. The mixture was then vacuum dried at 60℃ to constant weight to obtain 80g of powdered affinity recognition unit.

[0047] S2: Preparation of casting solution and membrane formation. 600g of PI was dissolved in 2400mL of DMF and stirred at 75℃ and 200r / min to prepare a 20% (w / w) PI solution. The solution was cooled to 40℃, and 120g of the powdered modified size sieve unit and 80g of the powdered affinity recognition unit were added. The mixture was stirred for 3h. 4.8g of AIBN (0.8% of the PI mass) and 1.8g of MBA (0.3% of the PI mass) were added, and stirring continued for 2h. The mixture was then ultrasonically degassed for 20min (300W) to obtain the casting solution. The casting solution was cast onto a pretreated support at a rate of 7.5cm / min, controlling the wet film thickness to 80μm. The film was allowed to stand at 25℃ and 40% relative humidity for 24h to evaporate and form a membrane; then dried at 80℃ for 3h; finally, thermal crosslinking was performed by heating to 150℃ at 5℃ / min and holding for 2h to obtain the initial composite membrane.

[0048] S3: Defect Repair. After the initial composite membrane cooled to room temperature, it was soaked in 2% dilute hydrochloric acid at 25°C for 2 hours, washed with deionized water until neutral, and vacuum dried at 70°C for 3 hours. Then, it was placed in a NaA zeolite precursor solution and reacted at 60°C for 3 hours to allow the zeolite nuclei to grow in situ and form NaA zeolite. Subsequently, the membrane material was placed in a 1 mol / L KCl solution and soaked at 60°C for 4 hours to perform potassium ion exchange, converting it into KA zeolite (effective pore size approximately 0.3 nm), resulting in the finished membrane with a thickness of 80 μm and an effective pore size range of 0.30-0.35 nm.

[0049] Example 3 This example provides a method for preparing hydrogen-nitrogen separation membrane materials based on size sieving and affinity recognition, including the following steps: S1: Raw material preparation. Size sieving unit: 120g of hydrogen-bonded organic framework HOF-16 (pore size 0.36nm), 60g of ZIF-8 zeolite (pore size 0.34nm), total 180g (mass ratio 2:1); Affinity recognition unit: 24g of palladium nanoparticles (particle size 15nm), 120g of amino-functionalized graphene, total 144g (mass ratio 1:5); Polymer matrix: 800g of polyimide.

[0050] Modification of size sieve unit: 180g of size sieve unit was added to 1020mL of deionized water and ultrasonically dispersed for 60min (power 500W) to prepare a dispersion with a mass concentration of 15%; 10.8g of KH-550 (accounting for 6% of the total mass of size sieve unit) was added, and the pH was adjusted to 7.0 with dilute NaOH. The mixture was stirred at 60℃ and 300r / min for 1h; it was then vacuum dried at 60℃ to constant weight to obtain 180g of powdered modified size sieve unit.

[0051] Affinity recognition unit dispersion: 144g of affinity recognition unit was added to approximately 1300mL of deionized water, and 2.16g of sodium dodecylbenzenesulfonate (1.5% of the total mass of affinity recognition unit) was added. The mixture was ultrasonically dispersed for 80min (500W) to prepare a dispersion with a mass concentration of approximately 10%. 0.72g of PVP (0.5% of the total mass of affinity recognition unit) was added, stirred to dissolve, and allowed to stand at 40℃ for 1h. The mixture was then vacuum dried at 60℃ to constant weight to obtain 144g of powdered affinity recognition unit.

[0052] S2: Preparation of casting solution and membrane formation. 800g of PI was dissolved in 2400mL of DMF and stirred at 75℃ and 200r / min to prepare a PI solution with a mass concentration of 25%. The solution was cooled to 50℃, and 180g of the powdered modified size sieve unit and 144g of the powdered affinity recognition unit were added. The mixture was stirred for 4h. 12g of AIBN (1.5% of the PI mass) and 6.4g of MBA (0.8% of the PI mass) were added, and stirring was continued for 1h. The mixture was then ultrasonically degassed for 30min (400W) to obtain the casting solution. The casting solution was cast onto a pretreated support at a rate of 7.5cm / min, controlling the wet film thickness to 120μm. The film was allowed to stand at 35℃ and 60% relative humidity for 12h to evaporate and form a membrane; then dried at 100℃ for 2h; finally, thermal crosslinking was performed by heating to 180℃ at 10℃ / min and holding for 1h to obtain the initial composite membrane.

[0053] S3: Defect Repair. After the initial composite membrane was cooled to room temperature, it was soaked in 5% dilute hydrochloric acid at 30°C for 1 hour, washed with deionized water until neutral, and vacuum dried at 80°C for 2 hours. Then, it was placed in a NaA zeolite precursor solution and reacted at 70°C for 2 hours to allow the zeolite nuclei to grow in situ and form NaA zeolite. Subsequently, the membrane material was placed in a 1 mol / L KCl solution and soaked at 60°C for 4 hours to perform potassium ion exchange, converting it into KA zeolite (effective pore size approximately 0.3 nm), resulting in the finished membrane with a thickness of 120 μm and an effective pore size range of 0.30-0.38 nm.

[0054] Comparative Example 1 This example provides a method for preparing a hydrogen-nitrogen separation membrane material, including the following steps: S1: Raw material preparation. Size sieving unit: HOF-16 hydrogen-bonded organic framework (pore size 0.36nm) 90g, ZIF-8 zeolite (pore size 0.34nm) 60g, total 150g (mass ratio 1.5:1); Polymer matrix (PI): polyimide 750g.

[0055] Modification of size sieve unit: 150g of size sieve unit was added to 850mL of deionized water and ultrasonically dispersed for 45min (power 400W) to prepare a dispersion with a mass concentration of 15%; 6.75g of KH-550 (accounting for 4.5% of the total mass of size sieve unit) was added, and the pH was adjusted to 6.5 with dilute hydrochloric acid. The mixture was stirred at 55℃ and 250r / min for 1.2h; the resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 150g of powdered modified size sieve unit.

[0056] S2: Preparation of casting solution and membrane formation. 750g of PI was dissolved in 2250mL of DMF and stirred at 75℃ and 200r / min to prepare a 25% (w / w) PI solution. The solution was cooled to 45℃, and 150g of the aforementioned powdered modified size sieve unit was added. The mixture was stirred for 3.5h. 9g of AIBN (1.2% of PI mass) and 3.75g of MBA (0.5% of PI mass) were added, and stirring continued for 1.5h. The mixture was then ultrasonically degassed for 25min (350W) to obtain the casting solution. The casting solution was cast onto a pretreated support at a rate of 7.5cm / min, controlling the wet film thickness to 100μm. The film was allowed to stand at 30℃ and 50% relative humidity for 18h to evaporate and form a membrane; then dried at 90℃ for 2.5h; finally, the temperature was increased to 165℃ at 7.5℃ / min and held for 1.5h for thermal crosslinking to obtain the initial composite membrane.

[0057] S3: Defect Repair. After the initial composite membrane cooled to room temperature, it was soaked in 3.5% dilute hydrochloric acid at 27°C for 1.5 hours, washed with deionized water until neutral, and vacuum dried at 75°C for 2.5 hours. Then, it was placed in a NaA zeolite precursor solution and reacted at 65°C for 2.5 hours to allow the zeolite nuclei to grow in situ and form NaA zeolite. Subsequently, the membrane material was placed in a 1 mol / L KCl solution and soaked at 60°C for 4 hours to perform potassium ion exchange, converting NaA zeolite into KA zeolite (effective pore size approximately 0.3 nm), resulting in the finished membrane with a thickness of 100 μm and an effective pore size range of 0.30-0.36 nm.

[0058] Comparative Example 2 This example provides a method for preparing a hydrogen-nitrogen separation membrane material, including the following steps: S1: Raw material preparation. Affinity recognition unit: 25g palladium nanoparticles (10nm particle size), 100g amino-functionalized graphene, total 125g (mass ratio 1:4); Polymer matrix (PI): 750g polyimide.

[0059] Affinity recognition unit dispersion: 125g of affinity recognition unit was added to approximately 1450mL of deionized water, and 1.88g of sodium dodecylbenzenesulfonate (1.5% of the total mass of affinity recognition unit) was added. The mixture was ultrasonically dispersed for 60min (400W) to prepare a dispersion with a mass concentration of approximately 8%. 0.75g of PVP (0.6% of the total mass of affinity recognition unit) was added, stirred to dissolve, and allowed to stand at 35℃ for 1.5h. The resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 125g of powdered affinity recognition unit.

[0060] S2: Preparation of casting solution and membrane formation. 750g of PI was dissolved in 2250mL of DMF and stirred at 75℃ and 200r / min to prepare a 25% (w / w) PI solution. The solution was cooled to 45℃, and 125g of the powdered affinity recognition unit was added. The mixture was stirred for 3.5h. 9g of AIBN (1.2% of PI mass) and 3.75g of MBA (0.5% of PI mass) were added, and stirring continued for 1.5h. The mixture was then ultrasonically degassed for 25min (350W) to obtain the casting solution. The casting solution was cast onto a pretreated support at a rate of 7.5cm / min, controlling the wet film thickness to 100μm. The film was allowed to stand at 30℃ and 50% relative humidity for 18h to evaporate and form a membrane; then dried at 90℃ for 2.5h; finally, the temperature was increased to 165℃ at 7.5℃ / min and held for 1.5h for thermal crosslinking to obtain the initial composite membrane.

[0061] S3: Defect Repair. After the initial composite membrane cooled to room temperature, it was soaked in 3.5% dilute hydrochloric acid at 27°C for 1.5 hours, washed with deionized water until neutral, and vacuum dried at 75°C for 2.5 hours. Then, it was placed in a NaA zeolite precursor solution and reacted at 65°C for 2.5 hours to allow the zeolite nuclei to grow in situ and form NaA zeolite. Subsequently, the membrane material was placed in a 1 mol / L KCl solution and soaked at 60°C for 4 hours to perform potassium ion exchange, converting NaA zeolite into KA zeolite (effective pore size approximately 0.3 nm), resulting in the finished membrane with a thickness of 100 μm and an effective pore size range of 0.30-0.36 nm.

[0062] Comparative Example 3 This example provides a method for preparing a hydrogen-nitrogen separation membrane material, including the following steps: S1: Raw material preparation. Size sieving unit: HOF-16 hydrogen-bonded organic framework (pore size 0.36nm) 90g, ZIF-8 zeolite (pore size 0.34nm) 60g, total 150g (mass ratio 1.5:1); Affinity recognition unit: palladium nanoparticles (particle size 10nm) 25g, amino-functionalized graphene 100g, total 125g (mass ratio 1:4); Polymer matrix (PI): polyimide 750g.

[0063] Modification of size sieve unit: 150g of size sieve unit was added to 850mL of deionized water and ultrasonically dispersed for 45min (power 400W) to prepare a dispersion with a mass concentration of 15%; 6.75g of KH-550 (accounting for 4.5% of the total mass of size sieve unit) was added, and the pH was adjusted to 6.5 with dilute hydrochloric acid. The mixture was stirred at 55℃ and 250r / min for 1.2h; the resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 150g of powdered modified size sieve unit.

[0064] Affinity recognition unit dispersion: 125g of affinity recognition unit was added to approximately 1450mL of deionized water, and 1.88g of sodium dodecylbenzenesulfonate (1.5% of the total mass of affinity recognition unit) was added. The mixture was ultrasonically dispersed for 60min (400W) to prepare a dispersion with a mass concentration of approximately 8%. 0.75g of PVP (0.6% of the total mass of affinity recognition unit) was added, stirred to dissolve, and allowed to stand at 35℃ for 1.5h. The resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 125g of powdered affinity recognition unit.

[0065] S2: Preparation of casting solution and film forming. 750g of PI was dissolved in 2250mL of DMF and stirred at 75℃ and 200r / min to prepare a PI solution with a mass concentration of 25%. The solution was cooled to 45℃, and 150g of the above-mentioned powdered modified size sieve unit and 125g of powdered affinity recognition unit were added. The mixture was stirred and mixed for 3.5h. 9g of AIBN (1.2% of the PI mass) and 3.75g of MBA (0.5% of the PI mass) were added, and stirring was continued for 1.5h. The mixture was then ultrasonically degassed for 25min (350W) to obtain the casting solution. The casting solution was cast onto a pretreated support at a rate of 7.5cm / min, controlling the wet film thickness to 100μm. The film was allowed to stand at 30℃ and 50% relative humidity for 18 hours to evaporate and form a film; then dried at 90℃ for 2.5 hours; and then thermally crosslinked by heating to 165℃ at 7.5℃ / min and holding for 1.5 hours to obtain the initial composite film.

[0066] S3: After the initial composite membrane is cooled to room temperature, it is soaked in 3.5% dilute hydrochloric acid at 27°C for 1.5 hours, washed with deionized water until neutral, and then vacuum dried at 75°C for 2.5 hours. The finished membrane with a thickness of 100 μm is obtained.

[0067] Comparative Example 4 This example provides a method for preparing a hydrogen-nitrogen separation membrane material, including the following steps: S1: Raw material preparation. Size sieving unit: HOF-16 hydrogen-bonded organic framework (pore size 0.36nm) 90g, ZIF-8 zeolite (pore size 0.34nm) 60g, total 150g (mass ratio 1.5:1); Affinity recognition unit: palladium nanoparticles (particle size 10nm) 25g, amino-functionalized graphene 100g, total 125g (mass ratio 1:4); Polymer matrix (PI): polyimide 750g.

[0068] Pretreatment of size sieve unit: 150g of size sieve unit was added to 850mL of deionized water and ultrasonically dispersed for 45min (power 400W). The pH was adjusted to 6.5 with dilute hydrochloric acid and stirred at 55℃ and 250r / min for 1.2h. The resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 150g of powdered size sieve unit.

[0069] Affinity recognition unit dispersion: 125g of affinity recognition unit was added to approximately 1450mL of deionized water, and 1.88g of sodium dodecylbenzenesulfonate (1.5% of the total mass of affinity recognition unit) was added. The mixture was ultrasonically dispersed for 60min (400W) to prepare a dispersion with a mass concentration of approximately 8%. 0.75g of PVP (0.6% of the total mass of affinity recognition unit) was added, stirred to dissolve, and allowed to stand at 35℃ for 1.5h. The resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 125g of powdered affinity recognition unit.

[0070] S2: Preparation of casting solution and film forming. 750g of PI was dissolved in 2250mL of DMF and stirred at 75℃ and 200r / min to prepare a 25% (w / w) PI solution. The solution was cooled to 45℃, and 150g of the powdered size sieving unit and 125g of the powdered affinity recognition unit were added. The mixture was stirred for 3.5h. 9g of AIBN (1.2% of the PI mass) and 3.75g of MBA (0.5% of the PI mass) were added, and stirring was continued for 1.5h. The mixture was then ultrasonically degassed for 25min (350W) to obtain the casting solution. The casting solution was cast onto a pretreated support at a rate of 7.5cm / min, controlling the wet film thickness to 100μm. The film was allowed to stand at 30℃ and 50% relative humidity for 18 hours to evaporate and form a film; then dried at 90℃ for 2.5 hours; and then thermally crosslinked by heating to 165℃ at 7.5℃ / min and holding for 1.5 hours to obtain the initial composite film.

[0071] S3: Defect Repair. After the initial composite membrane cooled to room temperature, it was soaked in 3.5% dilute hydrochloric acid at 27°C for 1.5 hours, washed with deionized water until neutral, and vacuum dried at 75°C for 2.5 hours. Then, it was placed in a NaA zeolite precursor solution and reacted at 65°C for 2.5 hours to allow the zeolite nuclei to grow in situ and form NaA zeolite. Subsequently, the membrane material was placed in a 1 mol / L KCl solution and soaked at 60°C for 4 hours to perform potassium ion exchange, converting NaA zeolite into KA zeolite (effective pore size approximately 0.3 nm), resulting in the finished membrane with a thickness of 100 μm and an effective pore size range of 0.30-0.36 nm.

[0072] Comparative Example 5 This example provides a method for preparing a hydrogen-nitrogen separation membrane material, including the following steps: S1: Raw material preparation. Size sieving unit: HOF-16 hydrogen-bonded organic framework (pore size 0.36nm) 90g, ZIF-8 zeolite (pore size 0.34nm) 60g, total 150g (mass ratio 1.5:1); Affinity recognition unit: palladium nanoparticles (particle size 10nm) 25g; Polymer matrix (PI): polyimide 750g.

[0073] Modification of size sieve unit: 150g of size sieve unit was added to 850mL of deionized water and ultrasonically dispersed for 45min (power 400W) to prepare a dispersion with a mass concentration of 15%; 6.75g of KH-550 (accounting for 4.5% of the total mass of size sieve unit) was added, and the pH was adjusted to 6.5 with dilute hydrochloric acid. The mixture was stirred at 55℃ and 250r / min for 1.2h; the resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 150g of powdered modified size sieve unit.

[0074] Affinity recognition unit dispersion: 25g palladium nanoparticles were added to about 290mL of deionized water, and 0.38g sodium dodecylbenzenesulfonate was added. The mixture was ultrasonically dispersed for 60min to prepare a dispersion of about 8%. 0.15g PVP was added, stirred to dissolve, and allowed to stand at 35℃ for 1.5h. The mixture was then dried to obtain powder.

[0075] S2: Preparation of casting solution and film forming. 750g of PI was dissolved in 2250mL of DMF and stirred at 75℃ and 200r / min to prepare a PI solution with a mass concentration of 25%. The solution was cooled to 45℃, and 150g of the above-mentioned powdered modified size sieve unit and 25g of powdered affinity recognition unit were added. The mixture was stirred and mixed for 3.5h. 9g of AIBN (1.2% of the PI mass) and 3.75g of MBA (0.5% of the PI mass) were added, and stirring was continued for 1.5h. The mixture was then ultrasonically degassed for 25min (350W) to obtain the casting solution. The casting solution was cast onto a pretreated support at a rate of 7.5cm / min, controlling the wet film thickness to 100μm. The film was allowed to stand at 30℃ and 50% relative humidity for 18 hours to evaporate and form a film; then dried at 90℃ for 2.5 hours; and then thermally crosslinked by heating to 165℃ at 7.5℃ / min and holding for 1.5 hours to obtain the initial composite film.

[0076] S3: Defect Repair. After the initial composite membrane cooled to room temperature, it was soaked in 3.5% dilute hydrochloric acid at 27°C for 1.5 hours, washed with deionized water until neutral, and vacuum dried at 75°C for 2.5 hours. Then, it was placed in a NaA zeolite precursor solution and reacted at 65°C for 2.5 hours to allow the zeolite nuclei to grow in situ and form NaA zeolite. Subsequently, the membrane material was placed in a 1 mol / L KCl solution and soaked at 60°C for 4 hours to perform potassium ion exchange, converting NaA zeolite into KA zeolite (effective pore size approximately 0.3 nm), resulting in the finished membrane with a thickness of 100 μm and an effective pore size range of 0.30-0.36 nm.

[0077] Comparative Example 6 This example provides a method for preparing a hydrogen-nitrogen separation membrane material, including the following steps: S1: Raw material preparation. Size sieving unit: HOF-16 hydrogen-bonded organic framework (pore size 0.36nm) 90g, ZIF-8 zeolite (pore size 0.34nm) 60g, total 150g (mass ratio 1.5:1); Affinity recognition unit: palladium nanoparticles (particle size 10nm) 25g, amino-functionalized graphene 100g, total 125g (mass ratio 1:4); Polymer matrix (PI): polyimide 750g.

[0078] Modification of size sieve unit: 150g of size sieve unit was added to 850mL of deionized water and ultrasonically dispersed for 45min (power 400W) to prepare a dispersion with a mass concentration of 15%; 6.75g of KH-550 (accounting for 4.5% of the total mass of size sieve unit) was added, and the pH was adjusted to 6.5 with dilute hydrochloric acid. The mixture was stirred at 55℃ and 250r / min for 1.2h; the resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 150g of powdered modified size sieve unit.

[0079] Affinity recognition unit dispersion: 125g of affinity recognition unit was added to approximately 1450mL of deionized water, and 1.88g of sodium dodecylbenzenesulfonate (1.5% of the total mass of affinity recognition unit) was added. The mixture was ultrasonically dispersed for 60min (400W) to prepare a dispersion with a mass concentration of approximately 8%. 0.75g of PVP (0.6% of the total mass of affinity recognition unit) was added, stirred to dissolve, and allowed to stand at 35℃ for 1.5h. The resulting dispersion was vacuum dried at 60℃ to constant weight to obtain 125g of powdered affinity recognition unit.

[0080] S2: Preparation of casting solution and film forming. 750g of PI was dissolved in 2250mL of DMF and stirred at 75℃ and 200r / min to prepare a PI solution with a mass concentration of 25%. The solution was cooled to 45℃, and 150g of the above-mentioned powdered modified size sieve unit and 125g of powdered affinity recognition unit were added. The mixture was stirred and mixed for 3.5h. 9g of AIBN (1.2% of the PI mass) and 3.75g of MBA (0.5% of the PI mass) were added, and stirring was continued for 1.5h. The mixture was then ultrasonically degassed for 25min (350W) to obtain the casting solution. The casting solution was cast onto a pretreated support at a rate of 7.5cm / min, controlling the wet film thickness to 100μm. The film was allowed to stand at 30℃ and 50% relative humidity for 18 hours to evaporate and form a film; then dried at 90℃ for 2.5 hours; and then thermally crosslinked by heating to 165℃ at 7.5℃ / min and holding for 1.5 hours to obtain the initial composite film.

[0081] S3: Defect Repair. After the initial composite membrane is cooled to room temperature, it is soaked in 3.5% dilute hydrochloric acid at 27°C for 1.5 hours, washed with deionized water until neutral, and vacuum dried at 75°C for 2.5 hours. Then, the membrane is heat-treated at 200°C for 5 hours to obtain the finished membrane with a thickness of 100 μm and an effective pore size range of 0.30-0.36 nm.

[0082] The performance of the separation membrane materials prepared in Examples 1-3 and Comparative Examples 1-6 was tested: H2 permeability (the ability of a membrane material to allow hydrogen to pass through per unit pressure difference, per unit area, and per unit time): tested using the constant pressure variable volume method at 200℃ and a pressure difference of 0.5MPa, with units of 10. -7 mol / (Pa·m 2 ·s).

[0083] H2 / N2 selectivity (the ability of a membrane material to distinguish between hydrogen and nitrogen): the ratio of pure gas permeability under the same conditions; the higher the selectivity, the higher the purity of hydrogen and the less nitrogen residue in the separated product.

[0084] H2 purity: The volume fraction of H2 in the product gas after single-stage separation of the mixed gas (75% H2, 25% N2).

[0085] H2 recovery rate (how much hydrogen in the feed gas is successfully recovered through the membrane): A high recovery rate means high feed utilization and good economic benefits.

[0086] 1000h stability: Selective attenuation rate after continuous operation for 1000h in a mixed gas containing 5% CO2 at 200℃ and 6MPa.

[0087] 70-cycle decay rate: refers to the percentage of selective decay of H2 / N2 after rapid heating and cooling cycles from -20 to 200℃.

[0088] Mechanical strength: tensile strength (MPa).

[0089] Thermal decomposition temperature: The 5% weight loss temperature (°C) measured by the TGA method reflects the membrane's tolerance to high-temperature conditions. Applications such as ammonia cracking for hydrogen production can operate at temperatures up to 300°C, and the membrane must maintain its structural integrity at this temperature.

[0090] Table 1 Performance parameters of the separation membrane materials in each embodiment and comparative example

[0091] From Table 1, we can see that: 1. The separation membrane materials of Examples 1-3 possess both size sieving and affinity recognition functions. Their H2 permeability (514-523) and selectivity (13.2-13.6) are significantly higher than those of Comparative Example 1 (136, 11.5) and Comparative Example 2 (143, 10.6), demonstrating that the dual mechanisms of size sieving and affinity recognition can simultaneously and significantly improve throughput and separation accuracy. Examples 1-3 exhibit excellent and balanced performance under different formulations and process conditions, indicating that the method provided by this invention has a wide window of opportunity, strong repeatability, and can be adapted to different industrial application scenarios.

[0092] 2. Comparative Example 1 lacked palladium nanoparticles, resulting in a permeability of only 136. In Example 1, thanks to the selective affinity enhancement and interfacial diffusion promotion effect of palladium nanoparticles, the permeability increased by nearly 4 times, and the recovery rate reached as high as 98.5%. This demonstrates that the adsorption of palladium nanoparticles is the main driving force for promoting transport. It enriches hydrogen on the upstream side to form a concentration gradient, accelerating permeation without causing product loss, and instead pushing the recovery rate to the highest level.

[0093] 3. Comparative Example 2 lacks sized sieve channels; relying solely on the adsorption-desorption of palladium nanoparticles, nitrogen can still partially permeate, resulting in a selectivity of only 10.6. In the examples, the 0.30-0.38 nm pore system constructed with HOF-16 / ZIF-8 precisely sits between hydrogen (0.289 nm) and nitrogen (0.364 nm), forming a high-throughput, high-selectivity physical sieve network. This is crucial for achieving hydrogen purity exceeding 99.999%. This demonstrates that the sized sieve unit ensures an absolute barrier against nitrogen.

[0094] 4. Comparative Example 3, without defect repair, showed acceptable permeability but a selectivity that dropped to 12.2, and cracks appeared after 70 thermal cycles. Comparative Example 6, using traditional thermal annealing, could only partially fill defects and could not precisely seal pinholes larger than 0.3 nm; its selectivity (12.5) and stability were still significantly weaker than Example 1. This indicates that in-situ growth of KA zeolite (0.30 nm) acts like a precise molecular-level patch, sealing non-selective leaks while maintaining hydrogen flux. Simultaneously, these rigid zeolite patches can withstand alternating temperature stress, giving the membrane superior thermal shock fatigue resistance and achieving a lifespan exceeding 5000 hours.

[0095] 5. Comparative Example 4 did not modify the size sieving unit. Due to the poor interfacial compatibility between the filler and the polymer, some non-selective voids were caused. The selectivity (12.8) and stability (10% decay) were both lower than those of Example 1, indicating that the KH-550 modification plays an important role in improving the integrity of the membrane.

[0096] 6. In Comparative Example 5, the affinity recognition unit was not supported by amino-functionalized graphene, resulting in severe aggregation of palladium nanoparticles, which significantly reduced permeability and selectivity, and exhibited extremely poor stability (40% degradation after 500 hours). Microcracks appeared after 70 cycles, indicating that amino-functionalized graphene, as a dispersion carrier and reinforcing sheet, not only maintained the activity of palladium nanoparticles but also enhanced interfacial bonding and mechanical strength through amino groups, preventing membrane fatigue cracking.

[0097] In summary, this invention achieves multiple advantages of hydrogen separation membranes, such as ultra-high purity, high throughput, high stability, thermal shock resistance, and long lifespan, through the combination of four technical features: material selection, interface design, dual mechanism construction, and in-situ defect repair.

[0098] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing hydrogen-nitrogen separation membrane materials based on size sieving and affinity recognition, characterized in that: Includes the following steps: S1: The size screening unit is modified to enhance its compatibility with the polymer matrix, resulting in a modified size screening unit. The affinity recognition unit is dispersed to obtain a stable affinity recognition unit dispersion. The polymer matrix is ​​dissolved and mixed with the modified size sieving unit and the affinity recognition unit dispersion in a certain proportion. An initiator and a crosslinking agent are added to obtain a casting solution. The size sieving unit has a pore structure that matches the molecular size of hydrogen and nitrogen to achieve physical size sieving. The affinity recognition unit contains metal nanoparticles and their carriers that have a specific affinity for hydrogen. The metal nanoparticles act as selective affinity sites, enhancing the solubility of hydrogen in the membrane and providing interfacial diffusion channels to achieve selective and rapid hydrogen transport. The size sieving unit is a complex of hydrogen-bonded organic framework HOF-16 and ZIF-8 zeolite, the affinity recognition unit is a complex of palladium nanoparticles and amino-functionalized graphene, and the polymer matrix is ​​polyimide. S2: The casting solution is formed on a porous support and then thermally crosslinked and cured to form an initial composite membrane; S3: Defect repair of the initial composite membrane is carried out by in-situ growth method. The initial composite membrane is placed in zeolite precursor solution, so that zeolite grows on the membrane surface and at the tiny defects inside, and is transformed into zeolite with a pore size of less than 0.30nm to block the defects. Finally, a hydrogen-nitrogen separation membrane material with dual functions of size sieving and affinity recognition is obtained.

2. The method for preparing hydrogen-nitrogen separation membrane material based on size sieving and affinity recognition according to claim 1, characterized in that: The mass ratio of the hydrogen-bonded organic framework HOF-16 to ZIF-8 zeolite is (1-2):1; the pore size of the hydrogen-bonded organic framework HOF-16 is 0.35-0.38 nm, and the pore size of the ZIF-8 zeolite is 0.34 nm. The mass ratio of the palladium nanoparticles to the amino-functionalized graphene is 1:(3-5). The modifier used in the modification treatment is γ-aminopropyltriethoxysilane; The initiator is azobisisobutyronitrile; The crosslinking agent is N,N'-methylenebisacrylamide; The porous support is a porous α-Al2O3 support with a pore size of 0.1-0.2 μm and a porosity of 40%-60%.

3. The method for preparing hydrogen-nitrogen separation membrane material based on size sieving and affinity recognition according to claim 2, characterized in that: The modification process of the size screening unit is as follows: The dried size sieve unit is added to deionized water and ultrasonically dispersed to prepare a size sieve unit dispersion with a mass concentration of 10%-15%. A modifier is added at a mass of 3%-6% of the total mass of the size sieve unit. The pH of the size sieve unit dispersion is adjusted to 6.0-7.0, and the mixture is stirred at 50-60℃ for 1-1.5 hours to obtain a modified size sieve unit dispersion.

4. The method for preparing hydrogen-nitrogen separation membrane material based on size sieving and affinity recognition according to claim 2, characterized in that: The distributed processing steps of the affinity recognition unit are as follows: Add the dried affinity recognition unit to deionized water, add a dispersant, and ultrasonically disperse to prepare an affinity recognition unit dispersion with a mass concentration of 8%-12%. Add a protective agent at a mass of 0.5%-1.0% of the total mass of the affinity recognition unit. After stirring evenly, let it stand at a constant temperature of 30-40℃ for 1-2 hours to obtain a stable affinity recognition unit dispersion.

5. The method for preparing hydrogen-nitrogen separation membrane material based on size sieving and affinity recognition according to claim 2, characterized in that: The preparation steps of the casting solution are as follows: The dried polymer matrix was dissolved in DMF and stirred at 70-80℃ to prepare a polymer matrix solution with a mass concentration of 15%-25%. The temperature was lowered to 40-50℃, and the modified size sieve unit dispersion and affinity recognition unit dispersion were added and stirred to mix. Then, an initiator and a crosslinking agent were added. The amount of initiator added was 0.8%-1.5% of the polymer matrix mass, and the amount of crosslinking agent added was 0.3%-0.8% of the polymer matrix mass. After stirring, ultrasonic degassing was performed to obtain the casting solution. Among them, the ratio of the pure material mass of the added modified size sieving unit to the pure material mass of the polymer matrix is ​​controlled to be 1:(4-6), and the ratio of the pure material mass of the added affinity recognition unit to the pure material mass of the polymer matrix is ​​controlled to be 1:(5-8).

6. The method for preparing hydrogen-nitrogen separation membrane material based on size sieving and affinity recognition according to claim 2, characterized in that: In S2, the casting solution is uniformly coated onto the porous support using a casting method, with a coating thickness of 50-150 μm. The film formation conditions are: temperature 25-35℃, relative humidity 40%-60%, and standing for 12-24 hours. The thermal crosslinking reaction temperature is 150-180℃, and the temperature is maintained for 1-2 hours.

7. The method for preparing hydrogen-nitrogen separation membrane material based on size sieving and affinity recognition according to claim 2, characterized in that: The specific steps for defect repair are as follows: The initial composite membrane was soaked in dilute hydrochloric acid with a mass concentration of 2%-5%, washed with water, and dried. Then it was placed in a NaA zeolite precursor solution and reacted at 60-70℃ for 2-3 hours to allow nanoscale zeolite nuclei to grow in situ at the defects. Subsequently, it was transformed into KA zeolite with a pore size of 0.30nm to seal the defects.

8. The method for preparing hydrogen-nitrogen separation membrane material based on size sieving and affinity recognition according to any one of claims 1-7, characterized in that: The effective pore size range of the hydrogen-nitrogen separation membrane material is 0.30-0.38 nm, and the membrane thickness is 80-120 μm.

Citation Information

Patent Citations

  • Preparation method and application of palladium-ceramic-palladium bilayer composite membrane material

    CN108144460A

  • Metal-containing monatomic molecular sieve carbon membrane with high hydrogen selectivity and preparation method of metal-containing monatomic molecular sieve carbon membrane

    CN118634659A